Preexisting antibodies can protect against congenital cytomegalovirus infection in monkeys - Nelson, Cody S. (JCI Insight, 2017)
Human cytomegalovirus (HCMV) is the most common congenital infection and a known cause of microcephaly, sensorineural hearing loss, and cognitive impairment among newborns worldwide. Natural maternal HCMV immunity reduces the incidence of congenital infection, but does not prevent the disease altogether. We employed a nonhuman primate model of congenital CMV infection to investigate the ability of preexisting antibodies to protect against placental CMV transmission in the setting of primary maternal infection and subsequent viremia, which is required for placental virus exposure. Pregnant, CD4(+) T cell–depleted, rhesus CMV–seronegative (RhCMV-seronegative) rhesus monkeys were treated with either standardly produced hyperimmune globulin (HIG) from RhCMV-seropositive macaques or dose-optimized, potently RhCMV-neutralizing HIG prior to intravenous challenge with an RhCMV mixture. HIG passive infusion provided complete protection against fetal loss in both groups. The dose-optimized, RhCMV-neutralizing HIG additionally inhibited placental transmission of RhCMV and reduced viral replication and diversity. Our findings suggest that the presence of durable and potently neutralizing antibodies at the time of primary infection can prevent transmission of systemically replicating maternal RhCMV to the developing fetus, and therefore should be a primary target of vaccines to eliminate this neonatal infection.